Assessing net economic gains from domestic and industrial water supply: cases from NRLP schemes - Choudhury, Nirmalya; Patel, Ankit; Phansalkar, S. (2009)
This paper attempts to identify and evolve a method for valuing and estimating the net gains from domestic and industrial water supply from the interbasin transfer schemes contemplated in the National River Link Project (NRLP). An existing interbasin transfer (IBT) scheme, namely Indira Gandhi Nahar Project (IGNP) and a proposed IBT scheme namely Polavaram- Vijaywada (PV) Link Canal were chosen for detailed analyses. Secondary data were used for identifying the region and the populations that benefited from the schemes. Economic gains arising out of water supply to the actual or potentially benefited areas were estimated. The estimation involved assessment of current costs incurred by the people in the area, in terms of both paid-out costs and time spent in fetching water. The saving in time was valued at market wage rates prevalent in the area and paid-out costs were assessed in terms of current market prices, ignoring the administered prices involved. The gains to urban populations were assessed by estimating the reduction in energy costs incurred by municipal authorities in undertaking the supply. Amortized capital costs for putting necessary hardware for distributing water from the IBT schemes as well as operation and maintenance (O&M) costs of running these schemes were netted from the gains to obtain the figures for net economic gains. More indirect benefits such as reduced drudgery or improved educational performance as well as reduced health expenditure were recognized but were all ignored to ensure greater robustness in the estimates. Only net gains to the society were considered and hence gains arising out of creation of industrial estates within the commands were ignored since similar gains could also be obtained by locating these estates elsewhere. The net economic gains are seen to depend on both demographic features of the region and its ecology. Desert-like conditions of the IGNP-benefited areas tend to make the gains from domestic water supply schemes large, while similar gains in the Polavaram-Vijaywada areas are smaller. The net economic gains are of a significant order and would seem to indicate that, at least insofar as the dry areas of the country are concerned, these can perhaps exceed the gains due to increased agricultural production and hence could perhaps justify the creation of the schemes by themselves.